Retrospective study of transmissible venereal tumor in dogs in Paraíba, Northeastern Brazil - Souto, Erick Platiní Ferreira; Oliveira, Artefio Martins de; Garcia, Dlean da Silva; Dantas, Antonio Flávio Medeiros (Seven Editora, 2023)
The epidemiological, clinical, and anatomopathological aspects of the transmissible venereal tumor in dogs in Paraíba, Northeastern Brazil, are described. From January 2003 to December 2016, 35 cases of Venereal Transmissible Tumors in dogs were diagnosed at the Animal Pathology Laboratory of the Federal University of Campina Grande. Of these, 19 (54%) were females and 16 (46%) males, with ages ranging from 1 year to 14 years. The animals were predominantly of no defined breed 28 (80%) and peridomicile 18 (51%). Most of the tumors, 25 (71%), were located in the genital mucosa, distributed by the vulva, vagina, foreskin, and penis. Extragenital localization was observed in 10 (29%) cases, with tumors present in the skin, eye and periocular structures, and nasal cavity. Macroscopically, they were multilobular, exophytic, of varying sizes, red-white masses, sometimes with areas of hemorrhage and ulceration. In the histopathology, round neoplastic cells were visualized, with granular cytoplasm, loosely grouped and assuming arrangements in mantles. Therapeutic protocols were performed in 12 cases with vincristine sulfate, of which 5 (42%) presented total clinical recovery. The striking macroscopic and histopathological features allow an efficient diagnosis of the condition, especially when the tumor is located in the genital mucous membranes. Treatment with vincristine sulfate can promote full clinical recovery. DOI:https://doi.org/10.56238/alookdevelopv1-191